2013
DOI: 10.3354/ame01646
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial diversity in a large, temperate, heavily modified river, as determined by pyrosequencing

Abstract: Despite the importance of microbes in lotic systems, the structure and diversity of microbial communities in rivers are understudied. Biodiversities of bacterial communities within a large, heavily modified river (Ohio River) and a major tributary (Guyandotte River) were examined using next-generation pyrosequencing and classical ecological diversity indices. Nextgeneration pyrosequencing was used to determine percent abundance of 16S rRNA gene sequences from 6 sites in the Ohio River and 1 site in the Guyando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 41 publications
3
19
0
Order By: Relevance
“…These data parallel findings in the existing literature in which a consistent freshwater stream microbiome has been proposed (2,9,10,13,19,21,31), though the exact definition of this population and the nomenclature describing this phenomenon have been highly variable. For example, the "core" freshwater community of stream biofilms and sediment was defined by Besemer et al as taxa found in at least 50% of all samples (2).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These data parallel findings in the existing literature in which a consistent freshwater stream microbiome has been proposed (2,9,10,13,19,21,31), though the exact definition of this population and the nomenclature describing this phenomenon have been highly variable. For example, the "core" freshwater community of stream biofilms and sediment was defined by Besemer et al as taxa found in at least 50% of all samples (2).…”
Section: Discussionsupporting
confidence: 84%
“…(21). It is clear that a select and consistent set of taxa dominate freshwater habitats in fluvial systems at all scales (23,25,28,31). However, it is also clear that the abundances of these microbes can vary substantially, both within and between fluvial networks (28).…”
Section: Discussionmentioning
confidence: 99%
“…The relative importance of the Proteobacteria decreased significantly from March to April and this shift in total abundance was accompanied by a significant change in the composition of this group. The patterns observed here are consistent with previous studies that found Proteobacteria to be numerically dominant in river and lake habitats when bacterial communities are supported by allochthonous nutrient inputs, and to be less abundant when autochthonous nutrients are most important (Tang et al 2009, Schultz et al 2013. Most notably in March, β-Proteobacteria dominated both filter class communities.…”
Section: Changes In Bacterial Community Composition During Inflow Eventssupporting
confidence: 82%
“…Our knowledge of the ecology of lotic microbes is much less developed than our understanding of marine and lake microbial communities. In particular, there is currently limited knowledge of how microbial communities respond to the constantly shifting environmental conditions that are characteristic of river ecosystems (Curtis & Sloan 2004, Schultz et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…The springs of East district was mainly dominated by the bacteria Emticicia (14.83%). Emticicia is a gram-negative bacterial genus belongs to family Cytophagaceae and they are ubiquitous in the aquatic environment (Schultz et al ., 2013; Seo et al ., 2015; Nam et al ., 2016). A number of significant members from the genera were identified in aquatic systems viz.…”
Section: Discussionmentioning
confidence: 99%